Competitive Foods, Discrimination, and Participation in the National School Lunch Program - Bhatia, Rajiv (American Public Health Association, 2011)
Meals served through the National School Lunch Program (NSLP) must meet rigorous nutritional standards; however, barriers to student participation may limit the program's health and social equity benefits. Unsubsidized meals and food offerings competing with the NSLP offerings in school lunch environments may be lowering qualified student participation either directly or via identification of subsidized low-income students or stigmatization of the NSLP. We document a pilot intervention conducted in San Francisco in 2009 and 2010 that demonstrated gains in NSLP participation after removal of separate competitive à la carte lunch meal offerings. Our observations suggest the need for greater attention to the potential discriminatory effects of competitive foods and to the issue of stigma by school nutrition program administrators, researchers, regulators, and policymakers.